Anthropology of Education: an introduction - Lesley Bartlett; Claudia Triana (Universidade Federal do Rio Grande do Sul, 2020)
What is the anthropology of education, and what does it contribute to the study of education? Those questions orient this special issue of Educação & Realidade. Anthropologies of education vary around the world (Anderson-Levitt, 2012a). Indeed, as Elsie Rockwell (2002, p. 3) notes, "[...] the analytic categories used to construct ethnographic texts are not autonomous; they are rooted in the societies in which they are first used, and they reflect actual ways of constructing difference in those societies". Nonetheless, we might identify some fundamental commitments that have evolved over time.